Contribution of nuclear energy on new energy systems post Fukushima. (July 2015) - Kato, Yukitaka
Abstract: Nuclear energy contribution on new energy systems post Fukushima was discussed in this study. A new energy transformation concept based on carbon recycling, called the Active Carbon Recycling Energy System, ACRES, was proposed for a zero carbon dioxide emission process. ACRES is driven with consumption of primary energy that does not emit carbon dioxide such as nuclear and renewable energies. A smart ironmaking system based on ACRES, iACRES, was also proposed. Carbon monoxide was thermodynamically the first candidate for recycling carbon media in iACRES because it had higher energy densities than hydrogen and was highly compatible with conventional iron-making process. From a feasibly study of iACRES driven by high-temperature gas reactor had the most availability for conventional ironmaking processes in the stand point of energy output rate in comparison with solar energy system. It was expected that nuclear energy could contribution on conventional industrial processes by using ACRES as a new energy system post Fukushima. Highlights: Active carbon recycling energy system, ACRES, was proposed. ACRES was a candidates for future energy system post Fukushima. A smart ironmaking system using ACRES, iACRES, with HTGR was proposed.